Vitamin E models - The effect of heteroatom substitution in 2-ethyl-2-methyl chroman and 2-ethyl-2-methyl-6-hydroxychroman - Setiadi D.H.; Chasse Gregory Adam; Torday László; Varró András; Papp Gyula; Csizmadia Imre Gyula (2002)
The molecular conformations of shortened molecular models of vitamin E (tocopherol and tocotrienol) and their sulfur and selenium congeners were studied computationally at the DFT level of theory [B3LYP/6-31G(d)]. The sequence of stabilization by the various heteroatoms was found to be the following: O similar to Se > S. On the basis of the present structural results it seems that the seleno-congener of vitamin E is a distinct possibility.
Keywords: Farmakológia és gyógyszerészet